Effects of different starches on the physicochemical and sensory characteristics of extruded fish snacks - Abu Talib, A.; Russly, A.R.; Bakar, J.; Mahmud Ab. Rashid, N.K.; Ashari, R.; Shukri, R.; Wan Ibadullah, W.Z.; Mustapha, N.A.; M.R., Ismail-Fitry; Z.A., Nur Hanani (Rynnye Lyan Resources, 2024)
The market for snack foods is currently heading for healthier choices. Extrusion-based snacks made of starch are widespread but less nutrient-dense. Therefore, an effort to produce expanded snacks with higher protein was attempted. However, the physical properties of high protein extrudates are less desirable. Hence, different kind of starches were used in attempt to improve the physical properties of extrudates with high protein from scad fish. The objective of this study was to determine the effect of types and percentages of three starches, namely tapioca, sago and corn (50, 67, 75% db); on the physicochemical properties of extrudates from round scad fish powder (Decaptus madruasi). The formulations were extruded using a single screw extruder with a 3 mm circular die. The feeder and screw speed were maintained at 150 and 50 rpm, respectively. The barrel temperatures for each zone were 80°C (zone 1), 120°C (zone 2), 140°C (zone 3) and 160°C (zone 4). The results of the study revealed that all starch types at 75% increased the expansion ratio of extrudates to 47-56% compared with the inclusion of starches at 50%. All starch types at 75% also decreased the bulk density to 21-24% and hardness to 23-50% as compared to extrudates with the lowest amount of starch. The improvements in the physical properties were more prominent in the addition of tapioca starch. The highest amount of protein was found in extrudates with tapioca starch (20.8 to 30.4%). The sensory analysis and colour indicated similar results for all extrudates. The best formulation for the production of fish snacks was extrudates with 75% tapioca starch and 25% fish powder. The finding of this study is relevant and applicable in the production of high protein extrudates for children or health-conscious consumers, with the usage of tapioca starch to assist better expansion that improves the physical properties.